Relationship between the protein surface hydrophobicity and its partitioning behaviour in aqueous two-phase systems of polyethyleneglycol- dextran - Tubio, Gisela (2004)
In order to develop possible correlations to predict partioning behaviour of proteins, five mammalian albumins (goat, bovine, equine, human and pig ones) with similar physico-chemical properties (molecular mass and isoelectrical point) were chosen. Evaluation of the relationship between hydrophobicity and partitioning coefficient (Kr) in polyethylenglycol-dextran (PEG-DxT500) systems formed by polyethyleneglycols of different molecular mass (3350, 6000 and 10,000) was investigated by estimating relative surface hydrophobicity (So) with a fluorescent probe, 1 anilino-8-naphthalene sulfonate. No relationship between Kr and So was found for systems formed by PEG3350, while aqueous two-phase systems with PEG6000 and PEG10,000 gave better correlations. The results obtained may be explained on the basis of an increase in the interaction between the latter PEGs and the protein due to their higher hydrophobic character which increases as the PEG molecular mass does so. In this way, systems with PEGs of higher molecular mass give the highest resolution to exploit hydrophobicity in partitioning.